6\(β\)-hydroxygeniposide, a potent \(α\)-glucosidase inhibitor from Gardenia jasminoides growing in Viet Nam - Vu, Dinh Hoang; Nguyen, Khac Hung; Pham, Quang Duong; Nguyen, Thi Viet Thanh; Dinh, Thi Phuong Anh; Chu, Van Tan; Cao, Duc Tuan; Tran, Hong Ngoc; Truong, Gia Bao; Tran, Dai Lam (Vietnam Journal of Science and Technology, 2024)
According to the statistics of WHO in 2019, diabetes was one of the top 10 causes of death in Vietnam and the incidence increasing day by day has required more effective treatment methods. For a long time, natural products have played an important role in drug screening programs. \(Gardenia jasminoides\) belongs to the \(Gardenia\) genus of Rubiaceae family, in which previous research showed potential ability in diabetes treatment through various mechanisms. In this study, three iridoids were isolated from \(G.~jasminoides\) collected in Vietnam and the \(α\)-glucosidase inhibitory activity was evaluated for the first time. The results showed that 6\(β\)-hydroxygeniposide (2) expressed the strongest activity with IC50 at \(6.38 ± 0.12 \,μ\text{M}\), meanwhile geniposide (1) and 6\(α\)-hydroxygeniposide (3) were inactive. The inhibitory mechanism of 6\(β\)-hydroxygeniposide was revealed by molecular docking and molecular dynamics. 6\(β\)-hydroxygeniposide competed and blocked \(p\)-nitrophenyl-\(α\)-D-glucopyranoside substrate reaching the reaction center of the enzyme, which was expressed through lower non-bonds interacting energy and stable binding affinity.